Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve this problem, we need to find the value of [tex]\( k \)[/tex] such that the remainders of the polynomials [tex]\( kx^3 + 3x^2 - 3 \)[/tex] and [tex]\( 2x^3 - 5x + k \)[/tex] when divided by [tex]\( x-4 \)[/tex] are the same.
### Step-by-Step Solution:
1. Substitute [tex]\( x = 4 \)[/tex] into both polynomials and set their remainders equal:
- When a polynomial [tex]\( f(x) \)[/tex] is divided by [tex]\( x - a \)[/tex], the remainder is given by [tex]\( f(a) \)[/tex].
2. Calculate the remainder of [tex]\( kx^3 + 3x^2 - 3 \)[/tex] when [tex]\( x = 4 \)[/tex]:
[tex]\[ f(4) = k(4)^3 + 3(4)^2 - 3 = k \cdot 64 + 3 \cdot 16 - 3 \][/tex]
Simplify each term:
[tex]\[ f(4) = 64k + 48 - 3 \][/tex]
Combine the constants:
[tex]\[ f(4) = 64k + 45 \][/tex]
3. Calculate the remainder of [tex]\( 2x^3 - 5x + k \)[/tex] when [tex]\( x = 4 \)[/tex]:
[tex]\[ g(4) = 2(4)^3 - 5(4) + k = 2 \cdot 64 - 5 \cdot 4 + k \][/tex]
Simplify each term:
[tex]\[ g(4) = 128 - 20 + k \][/tex]
Combine the constants:
[tex]\[ g(4) = 108 + k \][/tex]
4. Set the remainders equal to each other and solve for [tex]\( k \)[/tex]:
We have:
[tex]\[ 64k + 45 = 108 + k \][/tex]
Solve for [tex]\( k \)[/tex]:
[tex]\[ 64k - k = 108 - 45 \][/tex]
Combine like terms:
[tex]\[ 63k = 63 \][/tex]
Divide both sides by 63:
[tex]\[ k = 1 \][/tex]
### Conclusion
Thus, the value of [tex]\( k \)[/tex] that ensures the remainders are the same for both polynomials when divided by [tex]\( x-4 \)[/tex] is:
[tex]\[ \boxed{1} \][/tex]
### Step-by-Step Solution:
1. Substitute [tex]\( x = 4 \)[/tex] into both polynomials and set their remainders equal:
- When a polynomial [tex]\( f(x) \)[/tex] is divided by [tex]\( x - a \)[/tex], the remainder is given by [tex]\( f(a) \)[/tex].
2. Calculate the remainder of [tex]\( kx^3 + 3x^2 - 3 \)[/tex] when [tex]\( x = 4 \)[/tex]:
[tex]\[ f(4) = k(4)^3 + 3(4)^2 - 3 = k \cdot 64 + 3 \cdot 16 - 3 \][/tex]
Simplify each term:
[tex]\[ f(4) = 64k + 48 - 3 \][/tex]
Combine the constants:
[tex]\[ f(4) = 64k + 45 \][/tex]
3. Calculate the remainder of [tex]\( 2x^3 - 5x + k \)[/tex] when [tex]\( x = 4 \)[/tex]:
[tex]\[ g(4) = 2(4)^3 - 5(4) + k = 2 \cdot 64 - 5 \cdot 4 + k \][/tex]
Simplify each term:
[tex]\[ g(4) = 128 - 20 + k \][/tex]
Combine the constants:
[tex]\[ g(4) = 108 + k \][/tex]
4. Set the remainders equal to each other and solve for [tex]\( k \)[/tex]:
We have:
[tex]\[ 64k + 45 = 108 + k \][/tex]
Solve for [tex]\( k \)[/tex]:
[tex]\[ 64k - k = 108 - 45 \][/tex]
Combine like terms:
[tex]\[ 63k = 63 \][/tex]
Divide both sides by 63:
[tex]\[ k = 1 \][/tex]
### Conclusion
Thus, the value of [tex]\( k \)[/tex] that ensures the remainders are the same for both polynomials when divided by [tex]\( x-4 \)[/tex] is:
[tex]\[ \boxed{1} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.